Assessment of the Level of Awareness of Households and Institutions on the Impacts of Premature End-of-Life Vehicles in Nairobi City County, Kenya - Okoth, Selelah; Nyukur, Elvin; Mulwa, Richard (Journal of Sustainable Development Law and Policy, 2025)
Over the years, Kenya has recorded an increase in the volumes of vehicles shipped into the country. Some of these vehicles end up being premature end-of-life vehicles (ELVs) mainly due to road accidents. These premature ELVS are poorly managed mostly parked in police station yards, garages, and some residential estates causing public health and environmental harm thus undermining achievement of sustainable development. There have been scattered efforts on their management through policies and legislation such as the Environmental Management and Coordination Act, 1999; the umbrella law on environment which is both generic and unable to sufficiently address premature ELVs. This paper provides findings from a study whose objective was to assess the level of awareness of households, public and private institutions on the impact of poor management of premature ELVs on social concerns, public health, and the environment; and implores on the need for responsive policy and legal frameworks. To this end, structured questionnaires were administered to a total of 170 households in Nairobi County while key informant interviews (n=88) were conducted in relevant government agencies viz. policy making institutions; regulators and enforcement agencies; and, garages, salvage companies, and insurance firms. A Likert scale (1-5), with 1 being totally unaware and 5 highly aware was used to gauge the level of awareness. The mean level of awareness was 3.87 and most respondents were above this level of knowledge about social impacts such as degradation of the aesthetic values associated with poorly managed premature ELVs. However, another majority was below the average awareness level of 3.87 on awareness of the environmental and public health impacts associated with poor management of the premature ELVs. The results of this study indicate the need for enhanced awareness programs and development of policy and legal frameworks for effective management of premature ELVs in Kenya.